Association between ABO blood group and HCV-related hepatocellular carcinoma risk in China. Issue 49 (December 2016) - Li, Xu; Xu, Hongqin; Ding, Zhongyang; Jin, Qinglong; Gao, Pujun
Abstract : Abstract: The ABO blood group has previously been reported to be associated with risk for certain malignancies; however, data about the risks for hepatocellular carcinoma (HCC) according to blood type are limited. Thus, we conducted a retrospective case–control study to investigate whether the ABO blood group contributes to hepatitis C virus (HCV) infection–induced HCC. From January 2010 to June 2016, 447 consecutive patients with chronic HCV infection were recruited. Of these patients, 217 had HCV-related HCC, and 230 had chronic hepatitis C (CHC) without HCC. We performed multivariate logistic regression to probe the association between the ABO blood group and HCC risk. Compared with subjects with blood type O, patients with blood type A had an adjusted odds ratio (AOR) of 3.301 (95% confidence interval [CI], 1.927–5.653) for HCC after adjusting for age and gender. We found statistically significant associations between blood type A and HCC risk for both men (AOR [95% CI] = 4.192 [1.959–8.973]) and women (AOR [95% CI] = 2.594 [1.231–5.466]), and for patients aged below 70 years (<60 years: AOR [95% CI] = 3.418 [1.338–8.734]; 60–69 years: AOR [95% CI] = 3.917 [1.730–8.867]). Thus, HCC risk is associated with ABO blood type in Chinese CHC patients, and CHC patients with blood type A are more susceptible to HCV-related HCC than patients with other blood types.